(untitled) (Majalah Kedokteran Bandung, 2023)
Otomycosis is a common fungal infection of the external auditory meatus frequently diagnosed in otolaryngology outpatient clinics. Resistance to antifungals is currently a significant concern, with intrinsic and acquired resistance increasing among isolates that cause fungal infections. The purpose of this research was to identify Candida species causing otomycosis and determine the pattern of antifungal susceptibility among these Candida species. A prospective study was conducted in the Margono Soekarjo General Hospital and Department of Microbiology, Faculty of Medicine, Universitas Jenderal Soedirman Purwokerto, Indonesia, from April – September 2022. Forty-seven (47) clinical samples of otomycosis were collected from 41 patients and then isolated bedside on fungal culture media and was prepared on an object glass for direct microscopic examination of the specimens. Fungal identification was performed using 10% potassium hydroxide (KOH) to observe fungal elements. Samples were cultured on Saboraud dextrose agar (SDA) media with chloramphenicol and Czapek dox agar. The Germ Tube Test was used to identify Candida while yeast-specific identification and antifungal susceptibility assay using a rapid commercial kit was applied for specific identification of the fungus. Antifungal susceptibility patterns were obtained using the Integral System Yeast Plus (ISYP) media pack. Candida parapsilosis was the most prevalent Candida species discovered in this study, accounting for approximately 41.66%, which was followed by Candida tropicalis (25%) and Candida krusei (12.5%), whereas Candida albicans only accounted for 4.1% of the specimens. All Candida species were sensitive to flucitosine and ketoconazole, whereas the voriconazole sensitivity rate reached 96%. This study concludes that Candida parapsilosis is the most prevalent species of Candida in otomycosis, and that all Candida species are sensitive to Flucitosine, ketoconazole, and voriconazole.